Medical Student Attitudes toward Complementary, Alternative and Integrative Medicine. (14th April 2011) - Abbott, Ryan B.; Hui, Ka-Kit; Hays, Ron D.; Mandel, Jess; Goldstein, Michael; Winegarden, Babbi; Glaser, Dale; Brunton, Laurence
Abstract : While the use of complementary, alternative and integrative medicine (CAIM) is substantial, it continues to exist at the periphery of allopathic medicine. Understanding the attitudes of medical students toward CAIM will be useful in understanding future integration of CAIM and allopathic medicine. This study was conducted to develop and evaluate an instrument and assess medical students' attitudes toward CAIM. The Complementary, Alternative and Integrative Medicine Attitudes Questionnaire (CAIMAQ) was developed by a panel of experts in CAIM, allopathic medicine, medical education and survey development. A total of 1770 CAIMAQ surveys (51% of US medical schools participated) were obtained in a national sample of medical students in 2007. Factor analysis of the CAIMAQ revealed five distinct attitudinal domains: desirability of CAIM therapies, progressive patient/physician health care roles, mind-body-spirit connection, principles of allostasis and a holistic understanding of disease. The students held the most positive attitude for the "mind-body-spirit connection" and the least positive for the "desirability of CAIM therapies". This study provided initial support for the reliability of the CAIMAQ. The survey results indicated that in general students responded more positively to the principles of CAIM than to CAIM treatment. A higher quality of CAIM-related medical education and expanded research into CAIM therapies would facilitate appropriate integration of CAIM into medical curricula. The most significant limitation of this study is a low response rate, and further work is required to assess more representative populations in order to determine whether the relationships found in this study are generalizable.